Politics and culture in the making of public space: Taksim Square, 1 May 1977, Istanbul - Baykan, Aysegul; Hatuka, Tali (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2010)
This paper analyses how political and cultural claims over public space are symbolic of the social and historical transformation of a society at large. As an example, we aim to show that symbols, monuments and live practices of civic participation in Taksim Square, Istanbul, are integral to national and global events, and to the discourses of significance that mark particular decades. Accordingly, we discuss the changing meaning and the role of Taksim Square starting from the symbolic declaration of secularism during the first decade of the republican era, to a space of mass politics during the 1970s and finally as a spectacle of globalisation by the beginning of the twenty-first century. The May Day celebration of 1977 that ended in violence is the focal point of our analysis. We argue that this event is an expression of the mass politics of an era of urbanisation and industrialisation in a developing society during the 1970s, during which time the military often intervened. The military coup of 1980 and the global processes of liberalisation in the post-1980 era have also marked the Taksim Square. With expressions of mass politics banned, the square has become a spectacle of tourism and a locus of global culture. Henceforth, through the analysis of Taksim Square, we aim to present space as layers of articulations and fragmentation in the political culture of the nation and as instrumental in the power dynamics of the historically significant social processes and groups.
Keywords: civic participation; urban space; appropriation; symbolic meaning of space; violence; political culture; Architecture; History; Social Sciences - Other Topics